The Impact of Plaza Indonesia Shopping Mall’s Attributes toward Customers’ Satisfaction - Andrea Marsha (iBuss Management, 2015)
This research study is accomplished to understand the impact of mall’s attributes of Plaza Indonesia towards customers’ satisfaction. Plaza Indonesia is known as a leading high-end mall in Jakarta and has other competitors to compete with. Plaza Indonesia needs to be innovative by improving the mall’s attributes such as its environment, convenience, retailers, service, and rewards in order to outstand others and increase their customers’ satisfaction.The sampling method of this research is using simple random sampling (150 samples), in which the sample is the visitors of Plaza Indonesia that have visited Plaza Indonesia at least twice. Then, it will be analyzed using SPSS multiple regression to see whether the mall’s attributes simultaneously impact the customers’ satisfaction. Also, to see which of the attributes is the most impactful to the customers’ satisfaction. The result of this research shows that all of the mall’s attributes have simultaneously significant impact toward customers’ satisfaction. Individually, service quality is the most significant attribute to impact customers satisfaction, whereas reward is the only attribute that is not significantly impactful to customers’ satisfaction.Keywords: Mall’s Attributes, Shopping Malls, Customers’ Satisfaction, Shopping.